Factor structure and psychometric properties of a Romanian translation of the drive for Muscularity Scale (DMS) in university men. (June 2018) - Swami, Viren; Vintila, Mona; Tudorel, Otilia; Goian, Cosmin; Barron, David
Highlights: Romanian Drive for Muscularity Scale (DMS) reduces to two factors. A model with two first-order factors and one higher-order factor had poor fit. A model with only two first-order factors had acceptable but mediocre fit. Factor scores had adequate internal consistency and convergent validity. Abstract: We examined the psychometric properties of a Romanian translation of the 15-item Drive for Muscularity Scale (DMS). Male university students from Romania ( N  = 343) completed the DMS, as well as measures of self-esteem, body appreciation, and muscle discrepancy. Exploratory factor analysis indicated that DMS scores reduced to two factors that related to muscularity-oriented attitudes and behaviours, with both first-order factors loading onto a higher-order factor. However, confirmatory factor analysis indicated that a model with two first-order factors and a higher-order factor had poor fit. A two-factor model without a higher-order construct achieved acceptable but mediocre fit. Scores on the two-factor DMS model had adequate internal consistency and demonstrated acceptable convergent validity (significant correlations with self-esteem, body appreciation, and muscle discrepancy). These results provide support for a two-factor model of DMS scores in a Romanian-speaking sample and extends the availability of the DMS to a rarely-examined linguistic group.